Big data analytics strategies for the smart grid - Stimmel, Carol L (CRC Press, 2015)
"A successful data analytics program is the only way utilities will be able to meet the challenges of a modernized grid that is responsive from an operational perspective and meets the demands of greenhouse gas legislation. This book addresses the needs of applying big data technologies and approaches, including Big Data cybersecurity, to the critical infrastructure that makes up the electrical utility grid. It explores the unique needs of electrical utility grids, including operational technology, IT, storage, processing, and transformation to a usable state that benefits the utility business and electricity consumers"--